A novel neurofilament light chain Simoa assay that can quantify age‐dependent changes in control plasma samples over small time periods. (20th December 2022) - Das, Shreyasee; Dewit, Nele; Blennow, Kaj; Zetterberg, Henrik; Vanmechelen, Eugeen
Abstract: Background: Neurofilament light chain (Nf‐L) is an established biomarker for axonal degeneration, and it is well documented that Nf‐L shows an age‐ dependent increase in plasma. Currently, all highly sensitive immunoassay formats to quantify Nf‐L in plasma are based on one antibody pair alone, i.e., the commercial UmanDiagnostics monoclonal antibodies. Methods: In the novel Nf‐L Simoa, we have used Fab fragments of ADx206 as the capture antibody coupled to paramagnetic beads and biotinylated NfL23 as the detector antibody. Routine plasma and serum samples were collected according to established preclinical guidelines at baseline (BL) and after 7‐8 months of follow‐up (FU) for 23 individuals. The age range of these individuals was between 22 and 70 years. Results: All plasma and serum samples could be quantified and the lower limit of quantification (LLOQ) of the novel immunoassay was 2.2 pg/mL. The average coefficient of variation for plasma Nf‐L concentrations was 8% and that for serum was 13%. The plasma and serum concentrations correlated significantly with concentrations obtained using the commercial Quanterix Nf‐L Simoa kit (Plasma: Spearman's rho= 0.93, p<0.0001; Serum: Spearman's rho= 0.92, p<0.0001). However, in contrast to the Quanterix assay, Nf‐L concentrations detected in serum were lower than in plasma. Since the age range of the individuals were between 22 to 70 years, we were able to observe a significant age‐dependent increase of Nf‐L at BL in plasma as well as in serum. Furthermore, a positive 5% average annual rate of change in the Nf‐L plasma concentrations can be discriminated from BL to FU with the current assay format. Therefore, in this cohort, Nf‐L plasma concentrations increase from BL to FU, consistent with data reported from other cohorts. Conclusion: The novel Nf‐L Simoa is precise and can be used to quantify small scale changes in Nf‐L plasma concentrations. Our assay measured lower concentrations of Nf‐L in serum than in plasma, although quantification of serum samples using this assay format probably requires further optimization.